Statistical analysis of the machining parameters in drilling of carbon fibre reinforced plastics (CFRP) composite with various drill types - Othman, A.R. (Pleiades Publishing, 2018)
In contrast to the machining of metallic materials, drilling of the fiber reinforced composite materials presented unique challenges as its cutting behavior differs in several aspects. This work presents an analysis to determine the drilling characteristics in carbon fiber reinforced plastics (CFRP) composite using HSS twist drill, HSS brad drill and carbide dagger drill. The study is based on Taguchiâs method and analysis of variance (ANOVA). The experiments were conducted to quantify the statistical contributions of the spindle speed and feed rate for those three drills. The results indicated that the feed rate is recognized to make the most significant contribution to the thrust force, which reflects the hole quality and tool wear. In overall, brad drill promoted better hole quality at the exit side. A low thrust force, insignificant hole defect and hence, better drill condition was obtained with this drill at a cutting speed of 800Â rpm and feed rate of 0.04Â mm/rev. Â© 2018, Springer Nature Singapore Pte Ltd.